Clinical exome sequencing uncovers a high frequency of Mendelian disorders in infants with stroke: A retrospective analysis. Issue 11 (6th September 2022) - Kumar, Runjun D.; Meng, Linyan; Liu, Pengfei; Miyake, Christina Y.; Worley, Kim C.; Bi, Weimin; Lalani, Seema R.
Abstract: Stroke causes significant disability and is a common cause of death worldwide. Previous studies have estimated that 1%–5% of stroke is attributable to monogenic etiologies. We set out to assess the utility of clinical exome sequencing (ES) in the evaluation of stroke. We retrospectively analyzed 124 individuals who received ES at the Baylor Genetics reference lab between 2012 and 2021 who had stroke as a major part of their reported phenotype. Ages ranged from 10 days to 69 years. 8.9% of the cohort received a diagnosis, including 25% of infants less than 1 year old; an additional 10.5% of the cohort received a probable diagnosis. We identified several syndromes that predispose to stroke such as COL4A1 ‐related brain small vessel disease, homocystinuria caused by CBS mutation, POLG ‐related disorders, TTC19 ‐linked mitochondrial disease, and RNASEH2A associated Aicardi‐Goutieres syndrome. We also observed pathogenic variants in NSD1, PKHD1, HRAS, and ATP13A2, which are genes rarely associated with stroke. Although stroke is a complex phenotype with varying pathologies and risk factors, these results show that use of exome sequencing can be highly relevant in stroke, especially for those presenting <1 year of age.